Price Formation in the Value Chain of Eggplant (Solanum melongena L.) in Córdoba, Colombia - Martínez-Reina, Antonio María (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This work aims to analyze the formation of prices within the eggplant chain in the department of Córdoba (Colombia). Data from the weekly wholesale series in the Montería market were obtained from the DANE weekly information system during the years 2020 and 2021. The other calculations for the links of retail intermediaries and wholesalers come from the proportions found in the socioeconomic characterization work of the production system. Engle and Granger cointegration techniques were used, and analysis of the relationships between the series. The integration of the links in the chain and its impact on price formation was determined. The results show that the integration of the value chain is lower between the farmer and the final consumer, which was demonstrated with an elasticity of 0.34. The integration of the chain shows the price transfers from one link to another and also makes clear the increase when the link is changed, so the difference between the value paid by the consumer and the one received by the farmer is notorious. The work concludes that commercialization increases without adding value to the product.